Comparative cytogenetics and rDNA organization in Cactaceae: insights from Armatocereus mataranus subsp. ancashensis - Luis G. Rojas; Marlon Garcia-Paitan; Gean Ciprian-Salcedo; María Siles; Alberto López (Plant Systematics and Evolution, 2026)
Cytogenetic data remain limited for many lineages of Cactaceae, constraining our understanding of chromosome evolution in this diverse family. Here, we combine newly generated cytogenetic and genome size data for Armatocereus mataranus subsp. ancashensis with a comparative dataset of ribosomal DNA (rDNA) organization across Cactaceae to examine patterns of locus number and chromosomal distribution. rDNA loci were analysed using fluorescence in situ hybridization (FISH) with 5S and 45S probes, and nuclear DNA content was estimated by flow cytometry. Somatic cells exhibited 2n = 22 chromosomes, consistent with a diploid condition based on x = 11. Two 5S rDNA loci were located on different chromosome pairs, while a single terminal 45S rDNA locus was detected on another pair. The diploid genome size was estimated at 2C = 2.73 pg, and flow cytometric profiles indicated the presence of endopolyploidy. Comparative analyses across Cactaceae show that rDNA locus number and chromosomal distribution in A. mataranus subsp. ancashensis are broadly consistent with patterns reported in both Cactoideae and Opuntioideae. These findings place the cytogenetic characteristics of this taxon within a broader comparative context and highlight patterns of both conservation and variation in rDNA organization across Cactaceae. Finally, these data may be useful as a cytogenetic reference for future conservation studies on A. mataranus subsp. ancashensis .